“NARRATIVIZING INJUSTICE” THROUGH FICTION - Nguyen, Anna (Art/Research International)

(untitled) (University of Alberta, 2021)
In this theoretical musing, I propose a methodological and normative framework for including fiction writing in interdisciplinary research. Reviewing some traditional literary and rhetorical analyses alongside social theory, I reflect on ways of reading and citing, which inform our own fiction writing practices. In the first section, I consider how to read the text seriously as the starting point of sharing literary social worlds, followed by a vignette of critiquing fiction through citations to subvert dominant narratives. I end with an aspirational call for academics to consider fiction as a space where inclusivity and narrativizing injustice must be centered.